Cover Picture: Terminal Alkenes as Versatile Chemical Reporter Groups for Metabolic Oligosaccharide Engineering (Chem. Eur. J. 50/2014). Issue 50 (8th December 2014) - Späte, Anne‐Katrin; Schart, Verena F.; Schöllkopf, Sophie; Niederwieser, Andrea; Wittmann, Valentin
<x xml:space="preserve">Abstract</x> Chemically modified mannosamine derivatives with side chains of different length terminated by alkenes were applied for metabolic oligosaccharide engineering (MOE). During MOE, the sugars are transformed by cells into the corresponding sialic acids and incorporated into cell‐surface glycoconjugates. As terminal alkenes can function as dienophiles during inverse‐electron‐demand Diels–Alder reactions, the sugars can be fluorescently labeled by ligation to a tetrazine conjugate. The compound with a butenyloxycarbonyl side chain leads to the optimal balance between incorporation efficiency and speed of the ligation reaction, resulting in the most intense fluorescence signal. For more details, see the Full Paper by V. Wittmann et al. on p. 16502 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>